Method for preparing nickel-cobalt-manganese precursor by reducing ternary positive electrode powder through cooperation of straw and lithium ion battery current collector aluminum
Through the thermal chemical treatment of the lithium-ion battery current collector aluminum, the problem of high energy consumption and high pollution in lithium-ion battery recycling is solved, and efficient lithium recycling and nickel-cobalt-manganese precursor preparation is achieved, which has the characteristics of low energy consumption, environmental protection and cost-effectiveness.
Patent Information
- Application Number
- CN202411474462.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-04
AI Technical Summary
The existing lithium-ion battery recycling technology has problems such as high energy consumption, high pollution and high cost, especially when efficiently recycling Li, Ni, Co, and Mn in ternary cathode materials.
The straw collaborative lithium-ion battery current collector aluminum is used for thermal chemical treatment, lithium is recovered by low-temperature calcination and carbonic acid water immersion, and nickel-cobalt-manganese precursor is prepared by alkali leach.
It realizes efficient recycling of the cathode material of lithium-ion batteries, low energy consumption, environmental protection, cost-effectiveness, and is suitable for industrial applications.
Smart Images

Figure CN119551742A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electronic waste resource utilization, and specifically relates to a method for preparing a nickel-cobalt-manganese precursor by utilizing straw in conjunction with aluminum reduction of a lithium-ion battery current collector. Background Art
[0002] The rapid development of the new energy vehicle industry has brought a series of challenges, one of which is the disposal of scrapped lithium batteries. As the number of lithium batteries continues to grow, the amount of scrapped lithium batteries will also increase. If these scrapped lithium batteries are not handled properly, they will not only pollute the environment, but also cause safety hazards.
[0003] At present, the commonly used methods for recycling waste lithium-ion battery positive electrode materials are pyrometallurgy and hydrometallurgy. The wet metallurgical method includes acid leaching, ammonia leaching, biological method and low eutectic solvent method. Although the hydrometallurgical method requires less energy than the pyrometallurgical method, it requires more reagents and produces water pollution. The pyrometallurgical recycling process is simple to operate, short in process, and has a large processing capacity. It is a relatively mature recycling process; but it has disadvantages such as high energy consumption and the generation of secondary polluting gases. Compared with the traditional pyrometallurgical process, the low-temperature thermochemical method is more environmentally friendly to recover metals and prepare precursors.
[0004] In general, nitrate roasting and carbon reduction roasting methods are usually used to achieve the selective conversion of Li, Ni, Co, and Mn in waste ternary lithium-ion batteries. After such roasting, Li is converted into soluble metal sulfates, nitrates, or carbonates, while Ni, Co, Mn, and other metals exist as insoluble metals or their oxides. Subsequently, Li can be separated from metals such as Ni, Co, and Mn by simple water leaching or low-acid leaching without any reducing agent. The patent "A method for recovering lithium carbonate from retired lithium-ion battery black powder by carbon thermal reduction" (Shao Penghui, CN113921931A) discloses a method for recovering lithium carbonate from retired lithium-ion battery black powder by carbon thermal reduction. The method uses negative electrode graphite as a reducing agent, directly crushes and screens retired lithium-ion batteries without discharging, disassembling, and separation to obtain black powder, and then recovers lithium by water leaching after roasting, but the temperature of carbon thermal reduction is high and a long roasting time is required, which consumes a lot of energy. The patent "A method for recovering lithium from waste lithium-ion batteries" (Dai Changsong et al., CN115818674A) discloses a method for recovering lithium carbonate by pyrolysis reduction of waste lithium-ion batteries. The method uses waste biomass as a reducing agent, mixes the positive electrode active material after alkaline leaching and roasting with the waste biomass, performs reduction roasting in a protective atmosphere, and recovers lithium carbonate after carbonate water leaching of the obtained roasted lithium-containing material. This method can achieve efficient recovery of lithium carbonate by carbonate water leaching under high solid-liquid ratio conditions, but it undergoes two-stage roasting and requires the use of more reducing agents, which has high energy consumption and increases costs. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to propose a method for preparing a nickel-cobalt-manganese precursor by reducing ternary positive electrode powder using straw in coordination with aluminum current collector for lithium-ion batteries. Considering that lithium-ion ternary positive electrode materials include active materials, binders, conductive carbon and aluminum current collectors, and it is difficult to separate active substances from current collectors, and at the same time, the amount of Al used in the positive electrode materials is very high and Al has the characteristics of reducing properties, the present invention uses aluminum current collectors for lithium-ion batteries and pyrolysis products of straw as reducing agents, which greatly reduces the amount of reducing agent required to be added and can complete roasting at a lower temperature, while avoiding the generation of difficult-to-handle lithium aluminate when aluminum is used as a reducing agent. When aluminum and carbon are present at the same time, a synergistic effect is generated, and reduction can be achieved at a lower temperature and easy-to-handle lithium carbonate is produced. The processing process has low energy consumption, the recycling method is green and environmentally friendly, economical and efficient, and the process is simple, which meets the requirements of industrial application in the recycling industry of waste lithium-ion battery positive electrode materials.
[0006] The present invention uses straw as biomass material, generates reducing gas during roasting, and the biochar reacts synergistically with the current collector aluminum to effectively separate Li from Ni, Co, and Mn in waste lithium-ion batteries, recovers valuable metal Li by a simple carbonate water leaching method, and can prepare nickel, cobalt, and manganese precursors by alkaline leaching. The technical solution of the present invention is specifically described as follows.
[0007] A method for preparing a nickel-cobalt-manganese precursor by using straw to synergize with aluminum, a current collector of a lithium-ion battery, to reduce ternary positive electrode powder. The waste lithium-ion batteries that have undergone discharge pretreatment are disassembled to obtain positive electrode sheets, which are then crushed to obtain waste lithium-ion battery positive electrode powder; the straw is crushed and sieved to obtain straw powder; the waste lithium-ion battery positive electrode powder and the straw powder are mixed and then subjected to thermochemical treatment; the reduced roasted powder is subjected to a carbonic acid water leaching method to recover a filtrate and a filter residue; the specific steps are as follows: (1) Discharging, drying and disassembling the waste ternary lithium-ion batteries in sequence to obtain positive electrode sheets, crushing the positive electrode sheets to obtain positive electrode powder A; crushing and sieving the straw to obtain straw powder B; (2) Grinding and mixing positive electrode powder A and straw powder B to obtain mixed powder C; (3) The mixed powder C is then placed in a tube furnace for calcination to obtain calcined powder D; (4) subjecting the roasted powder D to a carbonated water leaching treatment, and after the leaching is completed, subjecting the roasted powder D to a solid-liquid separation treatment to obtain a lithium-rich filtrate E and a filter residue F containing nickel-cobalt-manganese compounds; (5) The filter residue F is subjected to alkaline leaching treatment to obtain a nickel-cobalt-manganese precursor.
[0008] In the present invention, in step (1), the waste ternary lithium-ion battery is placed in a NaCl solution for discharge, and then vacuum dried at a temperature of 60-80°C. The separated positive electrode sheet is provided with a current collector aluminum foil. After crushing, the particle size of the positive electrode powder A is less than 0.15 mm, and the straw powder B is passed through 20 mesh.
[0009] In the present invention, in step (2), the mixed powder C is prepared by grinding the positive electrode powder A and the straw powder B for 3-10 minutes, and the mass ratio of the positive electrode powder A to the straw powder B is 1:0.1-1:6. Preferably, the mass ratio is 1:2-1:4.
[0010] In the present invention, in step (3), the calcination conditions are as follows: in a protective nitrogen atmosphere, the temperature is heated to 550-750°C at a heating rate of 8-15°C / min, then kept at this temperature for 30-150min, and then naturally cooled to room temperature, and the calcined powder D is taken out. Preferably, the heating rate is 10°C / min, the calcination temperature is 600-700°C, and the calcination time is 60-120min. More preferably, the calcination temperature is 650°C, and the calcination time is 90min.
[0011] In the present invention, in step (4), the conditions for the carbonate water leaching treatment are: according to the CO2 flow rate of 60ml / min and the liquid-solid ratio of 5:1-25:1mL / g, the roasted powder D is placed in water at a temperature of 30-80°C and stirred for leaching for 30-90min. After the leaching is completed, the lithium-rich filtrate E is filtered and dried to obtain a Li2CO3 product. Preferably, the liquid-solid ratio is 5:1-15:1mL / g, the stirring leaching temperature is 30-60°C, and the leaching time is 30-60min.
[0012] In the present invention, in step (5), the nickel, cobalt and manganese in the filter residue F exist as oxides, and the alkali leaching treatment is used to remove Al ions in the filter residue to obtain a nickel, cobalt and manganese precursor; the alkali leaching treatment conditions are: according to the liquid-solid ratio of 10:1-60:1mL / g, the filter residue F is placed in a NaOH solution with a concentration of 1-3mol / L, and leached at a temperature of 30-80°C for 30-90min. Preferably, the liquid-solid ratio is 30:1-50:1mL / g, the NaOH concentration is 2-3mol / L, the temperature is 60-80°C, and the time is 60-90min.
[0013] As mentioned above, the present invention uses biomass waste straw as a green reducing agent to drive carbon thermal reduction, and recovers metal resources from waste ternary lithium-ion battery positive electrode powder through a mild pyrometallurgical route. Furthermore, the lithium, nickel, cobalt and manganese elements in waste ternary lithium-ion batteries are recovered by a low-temperature roasting method. The current collector aluminum of the present invention can significantly reduce the roasting reduction temperature, and at the same time cooperate with the reducing gas and biochar produced by straw pyrolysis to produce lithium oxide or lithium carbonate before the difficult-to-treat lithium aluminate in the aluminothermic reduction process, while aluminum exists in the form of oxides; at the same time, lithium, nickel, cobalt and manganese elements can be separated by simple water leaching and alkaline leaching to obtain lithium carbonate and nickel, cobalt and manganese precursors, which can then be used to prepare new ternary positive electrode materials by adding elements for oxidation roasting.
[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The yield of straw in agricultural production reaches 40%~60%. This method uses the reducing gas and biochar produced by straw pyrolysis as reducing agents, providing technical support for better realizing the energy and resource utilization of straw.
[0015] (2) This method makes full use of the synergistic effect between the current collector aluminum and the straw reduction process, selectively separates the lithium carbonate, and makes the subsequent treatment process simpler. The entire recycling process is green and environmentally friendly, with simple process, and has significant economic, environmental and social benefits.
[0016] (3) This method is simple in process and uses low-temperature roasting-water immersion processes with low energy consumption and environmental friendliness. It also achieves efficient recycling of waste lithium battery positive electrode materials and has good environmental and economic benefits.
[0017] (4) The lithium carbonate and nickel-cobalt-manganese precursors recovered by the present invention can be re-invested in battery manufacturing, thus achieving a virtuous cycle of product-waste-product. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Illustrations of the waste lithium-ion battery used in the present invention (left picture) and the positive electrode sheet manually disassembled after discharge and drying (right picture).
[0019] Figure 2 These are the XRD graphs of the mixed powder C of m (high aluminum) : m (straw) = 1:4 of Example 1, the mixed powder C of m (high aluminum) : m (straw) = 1:0.1 of Comparative Example 3, the high aluminum positive electrode powder of Comparative Example 4, and the low aluminum positive electrode powder of Comparative Example 5 after calcination at 650°C for 90 min. DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with embodiments and drawings, but the present invention is not limited to the following embodiments.
[0021] Example 1 (1) The used ternary lithium-ion batteries were discharged in a 10 wt.% NaCl solution for 48 h and vacuum dried at 80 °C for 24 h. The disassembled positive electrode sheets with current collector aluminum foil were crushed to obtain positive electrode powder A with a particle size of <0.15 mm. The straw was crushed and passed through a 20-mesh sieve to obtain straw powder B.
[0022] (2) Weigh 2 g of positive electrode powder A and 8 g of straw powder into a mortar and grind for 5 min to obtain mixed powder C.
[0023] (3) Place the mixed powder C in a quartz boat and put it into a tube furnace. After sealing, ventilate with high-purity N2 for 15 minutes in advance. Heat to 650°C at a heating rate of 10°C / min in a protective nitrogen (99.999 vol.%) atmosphere for 90 minutes. After cooling to room temperature, take out the calcined powder D.
[0024] (4) The calcined powder D was placed in a beaker, deionized water was added at a liquid-to-solid ratio of 10 mL / g, CO2 was introduced at a flow rate of 60 ml / min, and the mixture was stirred at 300 r / min at 30 °C for 60 min. After filtration, a lithium-rich filtrate E and a filter residue F containing nickel-cobalt-manganese compounds were obtained.
[0025] (5) The beakers containing the filtrate E and the residue F are placed in an oven and evaporated to dryness to obtain Li2CO3 product and nickel-cobalt-manganese-containing compounds.
[0026] In this embodiment, the leaching rate of Li was measured by the lithium-rich filtrate E obtained after carbonated water leaching, and the leaching rate of Li was 96.83%. This is because the addition of straw provides reducing gas and biochar for the thermochemical reaction process. When the amount of carbon is sufficient, the leaching rate of Li is significantly improved. Figure 2 The XRD pattern also shows that when sufficient carbon is provided, there is a synergistic effect between aluminum and carbon, and lithium carbonate is generated first.
[0027] Example 2 (1) The used ternary lithium-ion batteries were discharged in a 10 wt.% NaCl solution for 48 h and vacuum dried at 80 °C for 24 h. The disassembled positive electrode sheets with current collector aluminum foil were crushed to obtain positive electrode powder A with a particle size of <0.15 mm. The straw was crushed and passed through a 20-mesh sieve to obtain straw powder B.
[0028] (2) Weigh 2 g of positive electrode powder A and 4 g of straw powder into a mortar and grind for 5 min to obtain mixed powder C.
[0029] (3) Place the mixed powder C in a quartz boat and put it into a tube furnace. After sealing, ventilate with high-purity N2 for 15 minutes in advance. Heat to 750°C at a heating rate of 10°C / min in a protective nitrogen (99.999 vol.%) atmosphere for 90 minutes. After cooling to room temperature, take out the calcined powder D.
[0030] (4) The calcined powder D was placed in a beaker, deionized water was added at a liquid-to-solid ratio of 10 mL / g, CO2 was introduced at a flow rate of 60 ml / min, and the mixture was stirred at 300 r / min at 30 °C for 60 min. After filtration, a lithium-rich filtrate E and a filter residue F containing nickel-cobalt-manganese compounds were obtained.
[0031] (5) The beakers containing the filtrate E and the residue F are placed in an oven and evaporated to dryness to obtain Li2CO3 product and nickel-cobalt-manganese-containing compounds.
[0032] After testing, in this embodiment, the leaching rate of Li is 90.15%. Compared with Example 1, the amount of straw powder B is reduced, but a higher roasting temperature is required to achieve a higher leaching rate. This may be due to the reduction in the amount of straw powder B, which makes the amount of reducing substances insufficient and cannot be completely reduced and converted. It also shows that increasing the amount of straw powder B can reduce energy consumption.
[0033] Comparative Example 1 (1) The used ternary lithium-ion batteries were discharged in a 10 wt.% NaCl solution for 48 h and vacuum dried at 80 °C for 24 h. The disassembled positive electrode sheets with current collector aluminum foil were crushed to obtain positive electrode powder A with a particle size of <0.15 mm. The straw was crushed and passed through a 20-mesh sieve to obtain straw powder B.
[0034] (2) Weigh 2 g of positive electrode powder A and 12 g of straw powder into a mortar and grind for 5 min to obtain mixed powder C.
[0035] (3) Place the mixed powder C in a quartz boat and put it into a tube furnace. After sealing, ventilate with high-purity N2 for 15 minutes in advance. Heat to 550°C at a heating rate of 10°C / min in a protective nitrogen (99.999 vol.%) atmosphere for 90 minutes. After cooling to room temperature, take out the calcined powder D.
[0036] (4) The calcined powder D was placed in a beaker, deionized water was added at a liquid-to-solid ratio of 10 mL / g, CO2 was introduced at a flow rate of 60 ml / min, and the mixture was stirred at 300 r / min at 30 °C for 60 min. After filtration, a lithium-rich filtrate E and a filter residue F containing nickel-cobalt-manganese compounds were obtained.
[0037] (5) The beakers containing the filtrate E and the residue F are placed in an oven and evaporated to dryness to obtain Li2CO3 product and nickel-cobalt-manganese-containing compounds.
[0038] After testing, the leaching rate of Li in this embodiment is 77.59%. Embodiment 2 shows that increasing the amount of straw powder B can reduce energy consumption, but excessive straw powder B is not conducive to roasting reduction and may even affect subsequent experiments.
[0039] Comparative Example 2 Other conditions were the same as those in Comparative Example 1, and mixed powder C was prepared by mixing 2 g of positive electrode powder (aluminum-free) and 12 g of straw powder.
[0040] After testing, the leaching rate of Li was 58.74%. When the positive electrode powder did not contain Al, only the reducing gas and biochar produced by the pyrolysis of straw powder were used as reducing agents. Compared with Example 3, it was found that the leaching rate of Li was lower, indicating that there was a synergistic effect between aluminum and the pyrolysis products of straw, and the presence of aluminum could generate more water-soluble lithium salts during the reaction.
[0041] Comparative Example 3 The other conditions were the same as those in Example 1. Mixed powder C was prepared by mixing 2 g of positive electrode powder A and 0.2 g of straw powder B. After testing, in this case, the leaching rate of Li was 64.71%. Figure 2 From the XRD pattern analysis, it can be seen that when the reducing gas and biochar provided by straw pyrolysis are insufficient, the aluminum in the roasting product mostly exists in the form of lithium aluminate, rather than easily soluble lithium carbonate.
[0042] Comparative Example 4 (1) The used ternary lithium-ion batteries were discharged in a 10 wt.% NaCl solution for 48 h and then vacuum dried at 80 °C for 24 h. The disassembled positive electrode sheets with current collector aluminum foil were crushed to obtain positive electrode powder A with a particle size of <0.15 mm.
[0043] (2) Place the positive electrode powder A in a quartz boat and put it into a tube furnace. After sealing, ventilate it with high-purity N2 for 15 minutes in advance. In a protective nitrogen (99.999 vol.%) atmosphere, heat it to 650°C at a heating rate of 10°C / min for 90 minutes. After cooling to room temperature, take out the calcined powder D.
[0044] The leaching rate of Li was 53.68% after testing. This is because during the aluminothermic reduction process, most of the lithium was converted into lithium aluminate instead of lithium carbonate, which is easy to handle. Figure 2 XRD analysis also shows that Al exists mostly in the form of two compounds: LiAlO2 and Al2O3.
[0045] Comparative Example 5 The other conditions were the same as those in Comparative Example 4. The positive electrode powder was sieved through a 200-mesh sieve, and the Al content was significantly reduced from 6.051% to 0.122% (Table 1). At this time, the Li leaching rate was only 9.04%, which shows that Al has a reducing effect on the ternary positive electrode powder, but the low-aluminum material cannot achieve complete conversion of the ternary positive electrode powder.
[0046] Table 1 Analysis of element contents of unscreened positive electrode powder, i.e., high-aluminum positive electrode powder, and screened positive electrode powder, i.e., low-aluminum positive electrode powder
[0047] By comparison, it can be seen that the present invention utilizes straw as a biomass material to cooperate with the current collector aluminum in the positive electrode material of waste ternary lithium-ion batteries to reduce the positive electrode powder to prepare a nickel-cobalt-manganese precursor. The addition of biochar and aluminum thermal reduction produce a synergistic effect, and easy-to-handle lithium carbonate is generated in the first step. Lithium carbonate can be obtained through a simple carbonate water leaching method, and then oxidized and roasted with the dried nickel-cobalt-manganese compound to obtain a new ternary positive electrode powder. The entire process is simple, green and environmentally friendly, and has strong industrial applicability.
Claims
1. A method for preparing a nickel-cobalt-manganese precursor by using straw to reduce ternary positive electrode powder in cooperation with aluminum current collector of lithium-ion batteries, characterized in that: The specific steps are as follows: (1) Discharging, drying and disassembling the waste ternary lithium-ion batteries in sequence to obtain positive electrode sheets, crushing the positive electrode sheets to obtain positive electrode powder A; crushing and sieving straw to obtain straw powder B; (2) Grinding and mixing positive electrode powder A and straw powder B to obtain mixed powder C; (3) The mixed powder C is then placed in a tube furnace for calcination to obtain calcined powder D; (4) subjecting the roasted powder D to a carbonated water leaching treatment, and after the leaching is completed, subjecting the roasted powder D to a solid-liquid separation treatment to obtain a lithium-rich filtrate E and a filter residue F containing nickel-cobalt-manganese compounds; (5) The filter residue F is subjected to alkaline leaching treatment to obtain a nickel-cobalt-manganese precursor.
2. The method according to claim 1, characterized in that In step (1), the waste ternary lithium-ion battery is discharged in a NaCl solution and then vacuum dried at a temperature of 60-80°C. The separated positive electrode sheet is provided with a current collector aluminum foil. The particle size of the positive electrode powder A after crushing is less than 0.15 mm; and the straw powder B is passed through a 20-mesh filter.
3. The method according to claim 1, characterized in that In step (2), the mixed powder C is prepared by grinding the positive electrode powder A and the straw powder B for 3-10 minutes, and the mass ratio of the positive electrode powder A to the straw powder B is 1:0.1-1:
6.
4. The method according to claim 3, characterized in that The mass ratio of positive electrode powder A to straw powder B is 1:2-1:
4.
5. The method according to claim 1, characterized in that In step (3), the calcination conditions are as follows: in a protective nitrogen atmosphere, heat to a temperature of 550-750°C at a heating rate of 8-15°C / min, keep warm for 30-150 minutes, and then naturally cool to room temperature, and take out the calcined powder D.
6. The method according to claim 5, characterized in that The calcination temperature is 600-700°C, and the calcination time is 60-120min.
7. The method according to claim 1, characterized in that In step (4), the conditions for the carbonate water leaching treatment are: according to the CO2 flow rate of 60 ml / min and the liquid-solid ratio of 5:1-25:1 mL / g, the roasted powder D is placed in water at a temperature of 30-80°C and stirred for leaching for 30-90 min. After the leaching is completed, the lithium-rich filtrate E is filtered and dried to obtain the Li2CO3 product.
8. The method according to claim 7, characterized in that The liquid-to-solid ratio is 5:1-15:1 mL / g, the leaching temperature is 30-60°C, and the leaching time is 30-60 min.
9. The method according to claim 1, characterized in that In step (5), the alkaline leaching treatment conditions are: according to the liquid-solid ratio of 10:1-60:1 mL / g, the filter residue F is placed in a NaOH solution with a concentration of 1-3 mol / L, and leached at a temperature of 30-80°C for 30-90 min to remove Al ions in the filter residue and obtain a nickel-cobalt-manganese precursor.
10. The method according to claim 9, characterized in that The liquid-to-solid ratio is 30:1-50:1 mL / g, the NaOH concentration is 2-3 mol / L, the leaching temperature is 60-80°C, and the leaching time is 60-90 min.
Citation Information
Cited By
Method for recovering valuable metals from waste lithium ion batteries
CN119979908A